FLEXOR TENDON REPAIR IN THE HAND - فندي غسان (Latakia University Journal -Medical Sciences Series, 2023)
The hand is a unique tool that man possesses and distinguishes it from the hands of other creatures by its ability to grasp and touch. Functional compatibility between the hand and the cerebral cortex achieves tremendous harmony that makes a person accomplish what he wants and pushes him daily to more creations. In view of the importance of the hand for humans, great importance has been given to its injuries, especially the tendon injury, due to the total or partial functional disability left behind, which is reflected on the individual and society. Repairs of Tendon injuries have made remarkable progress, and modern suture materials, methods, kinetic treatment methods, and antibiotics have been provided in the hope that a significant part of the functions of their injured hands will return to these patients. However, the relative disability caused by adhesions remains an important problem, and efforts are still heading towards the best. A basic knowledge of the anatomy of the flexor tendons, especially in the forearm, wrist, and hand, is assumed, as is an understanding of the essential biomechanical aspects of flexor digitorum profundus and sublimis function in the fingers. Methods: Research methods: the latest new studies and practical experiments on the primary and secondary repairs of the flexor tendons in the hand, studies on human cadavers of biomechanics of suture formation, suture materials used for repairs, suture formation techniques, and postoperative rehabilitation program. Results: The results of primary flexor tendon repair also are better than secondary repair or staged reconstruction with a graft. especially In zone II, the primary surgeon has the greatest influence on the final result. To make the decision and perform a primary repair, a surgeon should be sufficiently skilled to perform a tendon graft or tenolysis later if the primary repair fails. Conclusion: Exacting wound care is crucial. Primary repairs may be fail because of adhesions especially ,in the area of the pulleys. A peripheral suture increases the strength of the repair, and a four-strand core suture combined with a peripheral suture allows a postoperative routine of light active flexion with the wrist extended, leading to better function and fewer complications. Early active motion rehabilitation programs may have a beneficial effect on tendon healing and may reduce adhesion formation significantly.